Determination of Effective Factors on Power Requirement and Conveying Capacity of a Screw Conveyor under Three Paddy Grain Varieties - Ezzatollah Askari Asli-Ardeh; Ahmad Mohsenimanesh (The Scientific World Journal)
An experiment was conducted to investigate the effect of screw speed, inclination angle and variety on the required power, and conveying capacity of a screw conveyor. The experiment was designed with four levels of screw speed (600, 800, 1000, and 1200 rpm), five levels of inclination angle (0, 20, 40, 60, and 80∘), and three levels of variety (Alikazemi, Hashemi, and Khazar). The Length, diameter, and pitch of screw were 2, 0.78, and 0.5 m, respectively. The experimental design was a randomized complete block (RCB) with factorial layout. Maximum and minimum power requirements of tested screw conveyor were 99.29 and 81.16 Watt corresponding to conveying capacity of 3.210 and 1.975 ton/hour obtained for khazar and Alikazemi varieties, respectively. The results indicated that as screw inclination angle increased from 0 to 80∘, the conveying capacity decreased significantly from 3.581 to 0.932 t/h. It can be concluded that the most conveying capacity was 4.955 t/h at tests with khazar variety and conveyor inclination angle zero degree.